The Mapuche in Chile’s public image: a comparison from a visual perspective - Cruz Bravo, Carlos (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
With the intention of analyzing some aspects, events and figures that encompass the visual and the public in the political history of the conformation of the State of Chile, this essay reviews various historical and journalistic backgrounds to make its way in this comparison of the similarities present in the conformation of the Greek polis and the State of Chile with the Mapuche. In synthesis, this comparison focuses on aspects such as the mythological, since it analyzes the similarities in the origins of the notion of creation of the world between the Greek and the Mapuche; the paradoxical, focused mainly on the ’demonization’ of the Mapuche people together with the commercialization of their image as an original people; the present duality that can be perceived in the transition of the Mapuche image from hero to villain or from warrior to terrorist; and finally, to confront the look of the foreign and the Mapuche in the Chilean identity. The comparisons in this essay seek to reflect on the transformation and adequacy of the visual economy of the Mapuche with respect to the different interests that emerge throughout history in the relationship of the Mapuche people with the State of Chile and the consequences that emanate from this ambivalent relationship within the public communication of the Mapuche.